2013
DOI: 10.1148/radiol.13120800
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Variceal Bleeding and Shunt Patency: Prospective Randomized Controlled Trial of Transjugular Intrahepatic Portosystemic Shunt Alone or Combined with Coronary Vein Embolization

Abstract: The TIPS+E regimen may reduce the risk of recurrent variceal bleeding during the first 6 months after the TIPS procedure by preventing shunt dysfunction, which may improve liver function and quality of life. © RSNA, 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 22 publications
3
65
1
1
Order By: Relevance
“…Over 30% of patients experience post-TIPS hepatic encephalopathy due to increased levels of circulating ammonia and other metabolites from the gut; 70% of these patients experience hepatic encephalopathy within 3 months after TIPS placement (6). The second major complication is recurrent portal hypertension secondary to development of in-stent stenosis, despite improved patency with the advent of covered stents (7,8). Therefore, comprehensive and longitudinal hemodynamic monitoring of the portal system and the TIPS is needed to monitor stent patency and the fraction of blood flow that is diverted from the liver (9,10).…”
mentioning
confidence: 99%
“…Over 30% of patients experience post-TIPS hepatic encephalopathy due to increased levels of circulating ammonia and other metabolites from the gut; 70% of these patients experience hepatic encephalopathy within 3 months after TIPS placement (6). The second major complication is recurrent portal hypertension secondary to development of in-stent stenosis, despite improved patency with the advent of covered stents (7,8). Therefore, comprehensive and longitudinal hemodynamic monitoring of the portal system and the TIPS is needed to monitor stent patency and the fraction of blood flow that is diverted from the liver (9,10).…”
mentioning
confidence: 99%
“…Although the benefits of variceal embolization or sclerotherapy are still controversial (11), the geometry of the DIPS did not impact the ability to perform these adjunctive procedures. However, none of the patients underwent periumbilical varix embolization, which could be hindered by a caudally directed extrahepatic portal vein puncture site.…”
Section: Discussionmentioning
confidence: 98%
“…At our knowledge, no other studies showed such data. This could be explained by the fact that oesophageal or gastric post-TIPS varices create a competitive flow, leading to more risk of stent thrombosis or stenosis because of lower flow into the TIPS (38,39). Indeed, persistent flow into varices can be responsible for hemodynamic steal from the PV leading to slower flow into the TIPS shunt and potentially higher risk of in-stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%